Influence of personality disorders on sexual behaviours and response to treatment of psychogenic erectile dysfunction in phosphodiesterase 5 inhibitor non-responders - Cabello-García, Marina; Sánchez-Sandoval, Yolanda; García-Rojas, Antonio Daniel (Frontiers in Psychology, 2024)
Background: Personality disorders may influence sexual behaviours and sexual dysfunction. Aim: Our main objective was to analyse the influence of personality disorders (PDs) in patients with erectile dysfunction (ED) of psychological origin that fail to respond to andrological treatment with Phosphodiesterase-5 inhibitors (IPDE5), assessing whether there are differences in sexual behaviours and response to psychosexual treatment.Methods: The research is designed as an ex post facto retrospective study with two groups. A control group of 23 men with ED without personality disorders and a group of 51 men with both ED and PDs. Results: In the case sample, 34.30% of the participants presented more than one personality disorder. No significant differences were found in sexual behaviours except for heteromasturbation (men without PDs masturbated their partners more to satisfy them than men with PDs), and men with PDs considered themselves less premature ejaculators than the control group. Finally, 82.14% of the control group did well with psychosexual therapy compared to 53.85% of the PDs group. Conclusion: Psychosexual treatment of ED has a worse outcome if the men also have PDs. Strengths and Limitations: From a clinical standpoint, it is important to assess the presence of personality disorders in men with ED and to implement psychosexual strategies to improve the response to treatment in these cases. Confirmation of the results with a much larger sample becomes necessary.